0153 Innovative interprofessional simulation workshops at the mental-physical interface – a mixed methodsstudy of effectiveness. (2nd November 2015) - Fernando, Asanga; Attoe, Chris; Pathan, James; Jaye, Peter; Cross, Sean
Abstract : Background: Mental disorder is the single largest source of burden of disease in the UK. 1 Recent surveys have revealed the prevalence of mental disorders in general hospital inpatients to be greater than 40%. 2 Common 'physical' Illnesses have profound psychological consequences. The recent five year forward view of the NHS highlights the importance of integrating mental and physical healthcare. 3 Despite this, training remains distinctly separate, despite the government's mandate to Health Education England 4, which specifically highlights the need for better training for healthcare professionals managing mental-physical comorbidity – which this intervention provides. Methodology: An exciting and innovative study involving the design, implementation and evaluation of a series of one-day interprofessional and cross-disciplinary simulation based training programmes throughout south London. Initially focus groups 5 were held with different sets of healthcare professionals, on the difficulties around managing mental-physical comorbidity. The salient themes arising then guided the development of simulation scenarios. The second phase of the study consisted of one day interprofessional simulation programmes, using actors and high fidelity mannequins. Participants were Drs and nurses from general hospital, community and mental health settings concerned with the management of mental-physical comorbidity. The third phase was a 'pre' and 'post' intervention evaluation consisting of measurement of participants' confidence at managing patients with comorbidity, their knowledge and attitudes to mental health. Results: n = 78. There were statistically significant, positive changes to the confidence of participants managing patients with physical and mental health comorbidity, and similar, positive changes across the domains of knowledge and attitudes to mental disorder. Participants also felt the intervention greatly improved team-working, patient safety and communication skills. Conclusions: This study demonstrates that integrative training which is innovative, interprofessional and simulation based is a power fulmodality to improve the levels of confidence and knowledge in healthcare professionals managing patients with mental-physical comorbidity, whilst improving attitudes to mental disorder, team-working and patient safety. References: World Health Organization (2008) Global Burden of Disease Report . WHO (http://www.who.int/healthinfo/global_burden_disease/estimates_country/en/index.html ) Rothenhäusler HB. Mental disorders in general hospital patients. Psychiatr Danub. 2006;18(3-4):183–92 NHS England. Five year Forward View, 2014 Delivering high quality, effective, compassion ate care: Developing the right people with the right skills and the right values: A mandate from the government to Health Education England. 2014. https://www.gov.uk/government/uploads/system/uploads/attachment_data/file/310170/DH_HEE_Mandate.pdf Barbour RS. Making sense of focus groups. Med Educ. 2005;39:742–750